2014
DOI: 10.1093/ehjci/jeu135
|View full text |Cite
|
Sign up to set email alerts
|

Added value of hybrid myocardial perfusion SPECT and CT coronary angiography in the diagnosis of coronary artery disease

Abstract: Current analysis resembles clinical routine of layered testing and shows that hybrid SPECT/CCTA imaging has a substantially higher yield than standalone SPECT or CCTA in the diagnostic workup of patients suspected of significant CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…The limited number of studies on the diagnostic value of PET/CT seem to confirm the theoretical enhanced accuracy as compared with either modality alone [18, 19, 70, 71]. Other studies revealed analogous improvement of diagnostic performance when fusing SPECT and CCTA [72, 73]. It is shown that especially the moderate specificity of CCTA benefits from the use of hybrid imaging and results in a more judicious referral pattern for invasive coronary angiography [7476].…”
Section: Additive Value Of Hybrid Pet/ctmentioning
confidence: 98%
“…The limited number of studies on the diagnostic value of PET/CT seem to confirm the theoretical enhanced accuracy as compared with either modality alone [18, 19, 70, 71]. Other studies revealed analogous improvement of diagnostic performance when fusing SPECT and CCTA [72, 73]. It is shown that especially the moderate specificity of CCTA benefits from the use of hybrid imaging and results in a more judicious referral pattern for invasive coronary angiography [7476].…”
Section: Additive Value Of Hybrid Pet/ctmentioning
confidence: 98%
“…Hybrid techniques have given variable results in the assessment of patients with chest pain with some early positive55 results for the hybrid imaging technique. Radiation burden to the patient with a combined MPS and CTCA approach does require justification, as the dose may vary anywhere between 2 and 20 mSv depending on a large number of variables.…”
Section: Hybrid Imagingmentioning
confidence: 99%
“…In a recent study that analysed the incremental utility of CTCA, SPECT and their combination over ECG stress testing for the diagnosis of functionally significant CAD, the ECG stress testing C-statistic increased from 0.73 to 0.85 when adding SPECT alone, to 0.90 when adding CTCA alone and to 0.96 when adding hybrid SPECT/CTCA data 57. A similar study using hybrid PET/CT showed 98% accuracy for the detection of obstructive CAD using radiation doses <10 mSv in most patients 58.…”
Section: Applications Of Cctmentioning
confidence: 99%